BUAH MERAH (PANDANUS CONOIDEUS LAMK) BIORESOURCES PEGUNUNGAN TENGAH PAPUA: KEANEKARAGAMAN DAN UPAYA KONSERVASINYA - Wawo, Albert Husein; Lestari, Peni; Setyowati, Ninik (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACT The red fruit (Pandanus conoideus Lamk) is one of the local bioresources on the Central Highlands Region of Papua. Exploration to reveal the red fruit diversity in this region had been carried out in 2016 and 2017 which covers Kurima, Kurulu, Siepkosi, Wesaput and Kaninmbaga / Bokondini areas. The method used in exploration were interview the local residents, observations of plant morphology, soil, micro-climate, surrounding species, and collection of propagation material. The observed red fruit morphology includes; stem height and diameter, leaf length and width, and number of roots. Observation of fruit development was carried out at the Royal Biological Garden in Wamena (KRBW). The results of the exploration obtained 23 red fruit cultivars in the Central Highlands region of Papua. All cultivars grow in moist environments; the texture of the soil is clay mixed with sand and loam. The development of fruit from young fruit into ripe fruit takes 3-4 months which is divided into 3 stages. Ex-situ red fruit conservation efforts have been carried out at the Royal Biological Garden in Wamena (KRBW). Until now, 141 numbers of red fruits have been conserved in KRBW. The community has also cultivated a number of red fruit cultivars in their yard and garden such as Bergum, Maler, Wona and Wesi cultivars as in situ conservation. The four cultivars are very popular because the fruit is large and the oil content is more than other cultivars.  Keywords: Diversity, Red Fruit, Conservation, Royal Biological Garden in Wamena, Central Highlands Region of Papua